The European Union’s Cultural Policy: The New Tasks? - Chałubińska-Jentkiewicz, Katarzyna (Przegląd Strategiczny, 2016)
The debate on European cultural policy has only just begun. What is intended to be the object is unknown. Topics taken during the European Culture Congress have the general nature and are only an introduction to critical reflection on what today is the European culture. Even if the answer seems obvious that these cultures o f the Member States, we still do not know whether it will be called. “High culture”, remaining in the elite circle of interest, or so. “Pop culture”? Perhaps the answer is indirect, and refers to the culture that we do not know from the media, the internet, billboards and banner ads, but rather that which we know through membership in a particular social group, religious community, and most of all family.